2011
DOI: 10.2298/bah1103959m
|View full text |Cite
|
Sign up to set email alerts
|

Variability and correlation between basic quality parameters of raw cow milk

Abstract: In this paper the results of the analysis of the milk somatic cell count are presented, as well as correlation between the somatic cell count and content of certain chemical parameters in milk (milk proteins, fat, lactose and dry matter without fat) determined in collective samples of milk obtained from cows reared in intensive rearing system, during two production years. The research was carried out by control of collective milk samples from cows reared on family holdings. Somatic cell count, as well as the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
3
1
Order By: Relevance
“…In contrast to a negative correlation between fat content and SCC in our study, a positive relationship was found between fat content and logarithm of SCC in a study by Friggens and Rasmussen (2001). Strong correlations were calculated between the contents of protein and casein (r = 0.733; P<0.01) and FFDM (r = 0.791; P<0.01), which is in agreement with the relationship between the contents of protein and FFDM found by Memiši et al (2011). The content of protein was negatively correlated with SCC (r = -0.255; P<0.05).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast to a negative correlation between fat content and SCC in our study, a positive relationship was found between fat content and logarithm of SCC in a study by Friggens and Rasmussen (2001). Strong correlations were calculated between the contents of protein and casein (r = 0.733; P<0.01) and FFDM (r = 0.791; P<0.01), which is in agreement with the relationship between the contents of protein and FFDM found by Memiši et al (2011). The content of protein was negatively correlated with SCC (r = -0.255; P<0.05).…”
Section: Resultssupporting
confidence: 89%
“…The contents of fat and FFDM were moderately correlated in our study (r = 0.414; P<0.01). Similar values (r = 0.34; P<0.001) were previously determined for Holstein cows (Memiši et al (2011). The content of fat was correlated negatively with SCC (r = -0.279) and positively with FP (r = 0.282; P<0.05).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This cases show the importance of non-genetic factors on milk production markers. In addition to reaching high quantity, determination of somatic cell count (SCC) is regarded as the principal process for monitoring quality of cow milk [10][11][12] . Somatic cells are responsible for natural defence system and contain lymphocytes, macrophages, epithelium cells and polymorphonuclear cells [13] .…”
mentioning
confidence: 99%
“…Studies revealed that high SCC adversely affects milk composition and processing level [8,14] . It has been indicated that elevation of SCC from 50x10 3 cells/ml to 800x10 3 cells/ml caused to reduction in milk yield by 6.3% in primiparous cows and 9.6% in cows in the third or later parities [10] . Today, modern dairy industry encourages producers to obtain milk with low SCC via additional payments [8] .…”
mentioning
confidence: 99%